Description of a new species of cecidomyiid (Diptera: Cecidomyiidae) predator of mealybugs (hemiptera: Pseudococcidae) on sugarcane - Urso-Guimarães, Maria Virgínia; Cruz, Maiara Alexandre [UNESP]; Martinelli, Nilza Maria [UNESP]; Peronti, Ana Lúcia Gonzalez Benfatti [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2020)
Diadiplosis saccharum sp. nov. (Diptera: Cecidomyiidae) is described based on male and female prey on nymphs of mealybug Saccharicoccus sacchari (Cockerell) (Hemiptera: Pseudococcidae) on Saccharum spp. (Poaceae) in São Paulo State, Brazil. Herein, the genus is composed by 33 species. The key of the eight species of the Diadiplosis distributed in Brazil is updated.
Keywords: Biodiversity; Ecological association; Neotropical region; Predaceous insect; Taxonomy